CREATIVE MANAGEMENT AND STRATEGIC MANAGEMENT AS FACTORS IN FORMING A POSITIVE IMAGE OF A MODERN ENTERPRISE - OLIINYK, Alina; BIHDAN, Yеvhenii; NECHYTAILO, Mariana; RAZSUKOVSKA, Amina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines that in order for the enterprise to achieve sustainable and long-term positive business success, it is expedient to form a strong image. The possibility of the enterprise gaining a certain market power, protecting against competitors' attacks, consolidating positions in relation to substitute goods and facilitating access to resources is substantiated. It is noted that the image of the enterprise includes various elements that help maintain a unified and recognizable image in the eyes of consumers. It is important that all these elements are consistent with each other and reflect values and characteristics. It has been proven that a positive image plays an important role in the success of any enterprise on the market. This helps attract the attention of consumers and partners, increases trust in the brand and contributes to increased sales. In addition, a positive image can also facilitate access to necessary resources and can be an additional advantage in the market. All components of the image are aimed at achieving three main goals: achieving a high level of competence and efficiency in working with clients; creation and maintenance of such a positive image that forces consumers to trust the enterprise; establishing an emotional connection with the buyer and society. The behavior of the staff, their attitude to work and customers, corporate culture – all this significantly affects both the processes of image development and the possibilities of its effective implementation. Image-building efforts should be directed at internal and external audiences. The internal image of the enterprise is created by the relations of personnel and management, their general direction, and the social and psychological climate. External image is the perception and image of the enterprise among consumers, investors, competitors, financial institutions, suppliers and their reaction to this image.
Keywords: corporate image; economic sustainability; social sustainability; corporate reputation; long-term process